Edukasi Pencegahan Obesitas pada Siswa SMPN Kota Jambi - Tina Yuli Fatmawati; Ariyanto Ariyanto; Nel Efni (Jurnal Abdimas Kesehatan (JAK), 2022)
Adolescents are currently experiencing obesity because their lifestyle is much different, seen from the habit of consuming fast food. Teenagers nowadays prefer to consume fast food on the grounds of following trends, being practical and tastier. Basic Health Research data mentions obesity in adolescents aged 16-18 years with a category (BMI/U) of 4.0%, an increase from 2013 which was 1.6%. In West Kalimantan the prevalence of obesity in adolescents aged 16-18 years increased from only 1.0% in 2013 to 3.4% in 2018.  Jambi in 2017 there were 56.47% of the 1.7 million visitors at the Puskesmas. The purpose of this community service is to provide education to students in efforts to prevent obesity and to recognize and understand ideal body weight and body mass index. The initial survey on one of students, they have the habit of eating foods that contain fat such as fried snacks, fast food, don't like eating vegetables, plus for the past 2 years they have carried out online learning so they stay at home more, are less active physical activities such as sports at school or at home. One of the students had mild obesity. The service methods that will be applied are lectures, discussions, mentoring, persuasive communication, physical examinations including measuring height and weight, calculating BMI. The target of education is 25 students at SMP N 19 Jambi City Service activities are carried out in from November - January 2022. The results of the service are obtained after education there is an increase in students' knowledge about obesity and students are able to calculate ideal body weight